Integrating Ethnophysics and Technology in Traditional Egrang Games to Support Sustainable Education and Cultural Preservation - Nabila Nur Almaida Nasution; Lisa Lailatus Sa’diyah; Fitri Diana Devi; Dwikoranto; Nurita Apridiana Lestari; Khoirun Nisa’ (Journal of Innovative Technology and Sustainability Education, 2025)
Objective: This study aims to analyze the physics concepts embedded in the traditional Indonesian game Egrang, using an ethnophysical approach to support sustainable education and cultural preservation (SDGs 4 & 11). Technology integration is explored as a medium to preserve and modernize the game. Method: A descriptive qualitative method combined with field observation and online data collection. The study also incorporates conceptual use of digital tools such as motion simulation and 3D modeling to illustrate physical principles within the game. Results: Findings show that Egrang involves concepts like kinetic and potential energy, pressure, mechanical effort, and equilibrium. Traditionally made from bamboo or wood, modern Egrang is now constructed from metal. Technological enhancements, such as augmented reality or mobile simulations, offer the potential to make Egrang more accessible and engaging for students while preserving cultural values. Novelty: This study uniquely combines ethnophysics with digital technology to revive traditional games as educational tools. The integration supports interactive STEM learning while promoting local cultural heritage, providing a contemporary solution to sustain traditional knowledge in the digital era.